Collaborative Governance in Ecotourism Development: The Role of Political Actors and Institutional Challenges in Barru Regency - Asril, Muhammad; Nadir, Sakinah; Imran, Muh. (SIGn Journal of Social Science, 2025)
Ecotourism development in Barru Regency currently faces complex challenges stemming from the disparity between abundant natural resource potential and the readiness of regional government institutions. This study aims to identify and analyze the roles of government and non-government actors, while simultaneously dissecting the relationship between local political dynamics and the effectiveness of ecotourism policy in Barru Regency. The research method applied is a qualitative approach with an exploratory case study design, in which primary data were collected through in-depth interviews with key informants from the legislative and executive branches and local communities, using an interactive data analysis model. The results indicate that local political dynamics are the primary determinant of policy effectiveness, as budget politics prioritize large-scale physical infrastructure development over environmental conservation. This condition creates institutional challenges in the form of a regional regulatory vacuum, leading to bureaucratic fragmentation and confusion over authority among technical agencies within the executive branch. Empirical data show a drastic decline in visitation and revenue at government-owned tourism attractions, while the private sector is experiencing massive growth. The weakness of these formal state institutions prompts the emergence of grassroots initiatives from non-government actors at the village level who self-manage governance roles, although these initiatives are threatened by stagnation due to the absence of systemic support. This study concludes that collaborative governance practices in Barru Regency have not yet ideally materialized due to the absence of an inclusive decision-making forum. As a recommendation, the regional government must urgently draft a regional regulation mandating the establishment of a collaborative ecotourism council to synergize the roles of government, village, and private-sector managers into a single sustainable development vision.